If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 73x + -1 = 5x + -1 Reorder the terms: -1 + 73x = 5x + -1 Reorder the terms: -1 + 73x = -1 + 5x Add '1' to each side of the equation. -1 + 1 + 73x = -1 + 1 + 5x Combine like terms: -1 + 1 = 0 0 + 73x = -1 + 1 + 5x 73x = -1 + 1 + 5x Combine like terms: -1 + 1 = 0 73x = 0 + 5x 73x = 5x Solving 73x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 73x + -5x = 5x + -5x Combine like terms: 73x + -5x = 68x 68x = 5x + -5x Combine like terms: 5x + -5x = 0 68x = 0 Divide each side by '68'. x = 0 Simplifying x = 0
| v^2-7=0 | | -112+4x=100 | | 1/8m+2/5+1/2m=3/8m+3/4m | | 5x+2=67 | | 81x-5x=8x+16 | | r/3+3r | | 3r^2+19r+30=0 | | (3x^2+4y^2-7)-(9x^2+4y^2-6)=0 | | -15+4x+10z-75-z+7x= | | 5(f-32)/9 | | (c*18)+18(c-2)=92 | | 8y+1=4y+7 | | i=14600(.05*33) | | 0=-8v+17 | | 13=x/-3+5 | | i=14600(0.5*.33) | | S=3Lw+3wh+5hL | | 3x-6-3x+6=0.5x+10 | | x^2-9x=220 | | 5(t-14)+3(t+6)=-2(t+5)-2 | | x^2-13x=198 | | (6x-7/x)-(1/x^2)=5 | | 12y-4=3 | | 5a-8=29 | | x^2-15x=324 | | 15-x=2[x+3] | | -5/3m=45 | | -49=-5x+2(5x-2) | | (2x+7)(2x-7)= | | 8x+16=5x+1 | | -5/3m=60 | | x^2-18x=360 |